Analisis Pengaruh Intellectual Capital Dan Spiritual Capital Terhadap Pengelolaan Keuangan UMKM Kabupaten Tana Toraja - Trevi Claudia Lestari; Jemi Pabisangan Tahirs; Yohanis Lotong Ta'dung (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Trevi Claudia Lestari (2023). This study aims to determine the effect Intellectual Capital And Spiritual Capital on MSME financial management in Tana Toraja Regency . This study used a questionnaire distributed to SMEs in Regency Tana Torajan . Sampling using non-probability sampling with a purposive sampling approach . The data analysis technique used is linear regression analysis double . From the test results known Intellectual Capital (X1) And Spiritual Capital (X2) is influential positive And significant to MSME Finance (Y) . In the partial test results it is known that the value of t is calculated variable Intellectual Capital (X1) 2,762 is greater than t table 2,010 and the value is sig. 0.000 _ < 0.05 . On variable Spiritual Capital ( X2) 2,579 is greater than t table 2,010 and the sig value. 0.003 < 0.05 . While the test results of the coefficient of determination are known Intellectual Capital (X1) And Spiritual Capital (X2) has an effect of 58.2% and the remaining 41.8% is influenced by other variables outside of this study. Results test simultaneous show mark FcountÂ 5,102 more big from Ftable 4050 with sig . 0.004 < 0.05, then can is known that variable Intellectual Capital (X1) and Spiritual Capital (X2) is influential in a manner simultaneous to MSME Finance (Y).